A prospective, randomised, investigator-blind, controlled, clinical study on the clinical efficacy and tolerability of two highly purified hMG preparations administered subcutaneously in women undergoing IVF. (July 2013) - Alviggi, C.; Cognigni, G.E.; Morgante, G.; Cometti, B.; Ranieri, A.; Strina, I.; Filicori, M.; De Leo, V.; De Placido, G.
Abstract The aim of this multicentre, prospective, randomised, investigator blind, controlled clinical trial was to evaluate the clinical efficacy and tolerability of a highly purified human menopausal gonadotrophin (hMG) preparation (Merional-HG) when administered to patients undergoing controlled ovarian stimulation (COS) for in-vitro fertilisation (IVF) procedure enrolled in hospital departments. One hundred fifty-seven patients were randomised in two parallel groups: 78 started COS with Merional-HG and 79 with Menopur. Results of the study showed that both highly purified hMG preparations were equivalent in terms of number of oocytes retrieved (primary endpoint: 8.8 ± 3.9 versus 8.4 ± 3.8, p = 0.54). In the patients treated with Merional-HG, we observed a higher occurrence of mature oocytes (78.3% versus 71.4%, p = 0.005) and a reduced quantity of gonadotrophins administered per cycle (2.556 ± 636 IU versus 2.969 ± 855 IU, p < 0.001). Fertilisation, cleavage, implantation rates and the number of positive β-human chorionic gonadotrophin (hCG; pregnancy) tests and the clinical pregnancy rate were comparable in the two groups. Both treatments were well tolerated. In conclusion, the results of this study support the efficacy and safety of Merional-HG administered subcutaneously for assisted reproduction techniques. Efficiency of Merional-HG appears to be higher due to reduced quantity of drug used and the higher yield of mature oocytes retrieved.